Bisphenol A (BADCy)/bisphenol P (BPDCy) cyanate ester/colemanite composites: synthesis and characterization - KAHRAMAN, MEMET VEZİR; MADAKBAŞ, SEYFULLAH (SPRINGER, 2015)
The aim of this study was to improve thermal stability, mechanical, and surface properties of bisphenol A dicyanate ester (BADCy) with the addition of bisphenol P dicyanate ester (BPDCy) and colemanite. The cyanate esters (BADCy and BPDCy) were prepared from diphenol compound (bisphenol A or bisphenol P) and cyanogen bromide in the presence of triethylamine. The chemical structure of the synthesized cyanate esters was investigated by fourier transform infrared spectroscopy and nuclear magnetic resonance spectroscopy (H-1-NMR and C-13-NMR) techniques. The cyanate esters/colemanite composites having various ratios of BADCy, BPDCy, and colemanite were prepared. Thermal stability of the samples was evaluated by thermogravimetric analysis and differential scanning calorimetry. The samples were characterized with the following analyses: gel content, water absorption capacity, and stress-strain test. Hydrophobicity of the samples was determined by the contact angle measurements. Moreover, the surface morphology of the samples was investigated by a scanning electron microscopy-energy dispersive spectrometer mapping. Finally, the obtained results prove that the prepared composites have good thermal, mechanical, and surface properties and that they can be used in many applications such as the electronic devices, materials engineering, and other emergent.
Keywords: Cyanate esters; Colemanite; Composites; ESTER RESIN; EPOXY